Jetting of multiple functional materials by additive manufacturing - Ledesma Fernandez, Javier (2018)
The rise and consolidation of Additive Manufacturing (AM) as a technology has made possible the fabrication of highly customised and complex products in almost every industry. This not only allows the creation of objects that were impossible just a few decades ago but also facilitates the production of small runs of products at a reasonable cost, which reduces the design-prototyping cycles and boosts product innovation. However, to produce truly functional parts it is desirable for these systems to be able to deposit multiple complex materials in a single process to locally embed controllable properties such as electrical conductivity or sensing capabilities into the produced geometries. Consequently, a review of current AM technologies capable of depositing conductive materials is performed in this PhD and discussed to find the most suitable approaches. Similarly, existing multi-material set-ups are studied to find limitations and common practices to create a system that is capable of fulfilling the objectives of this work. Piezo-activated inkjet printing (PIJ) is identified as an appropriate technology for multi-material applications due to its non-contact nature, high spatial resolution, capability of mixing and digitally grading materials and simple scale-up of the process. Furthermore, in the last decade it has been shown that jetting can be used for the accurate deposition of a wide range of functional materials. However, upon detailed review of this method, the limitations that it imposes on the compositions of the inks are identified as its main drawback. Specifically, the solid content and molecular weight of the fluids that can be jetted are restricted by the viscosity of the final ink, typically under 40 mPa·s. This is problematic in the case of jetting conductive materials, since it forces the solid content to be very low, therefore yielding very thin and often inhomogeneous layers. Additionally, all the organic components on the inks added to facilitate its ejection need to be removed, which typically means longer and more aggressive post-processes before rendering the printed tracks conductive. For this reason, drop-on-demand micro-dispensing valves were chosen as a high viscosity jetting (HVJ) approach in this work, with the intention of assessing their capability as a suitable tool for multi-material AM of functional inks. However, since their resolution and speed are lower than conventional inkjet, a hybrid approach is presented including micro-dispensing valves and inkjet printheads capable of depositing a wide range of viscosities in a single process. A comprehensive description of the hybrid set-up is given, discussing its main elements including the printing heads, the custom design printer assembly, the ultraviolet (UV) and infrared (IR) lamps installed for in-situ processing, the monitoring system and the set-up to measure the evolution of the electrical resistance in printed tracks in real time during post-processing. Additionally, the printing strategy and process flow is discussed. The investigated set-up was used to study the printability and performance of several functional materials ranging from UV-curable polymers to conductive formulations such as carbon paint, a silver nanoparticle-based paste and a dispersion of PEDOT:PSS. Each material was thoroughly characterised prior to printing with a special focus on viscosity. Their drop formation and deposition processes were studied at different printing settings using high speed imaging and footprint analysis of the deposited drops. These tests were used to obtain sets of working parameters that allow reliable printing and were used to produce 2D patterns with different resolutions to find the drop spacing that results in flat homogeneous films. Later, these films were post-treated according to the requirements of each material and multilayer structures were produced and analysed with an optical profilometer. The cross-section of these 3D tracks was used together with the measured resistance to obtain the electric conductivity of the materials under the printing conditions used. Finally, the accumulated information during the previous stages of printing was used to produce 3D multi-material demonstrators with incorporated conductive tracks, electric components and electroluminescent elements. These proof-of-concept samples were used to discuss limitations of the approach and showcase future possibilities of the system.